Glioma‐astrocyte interactions on white matter tract‐mimetic aligned electrospun nanofibers. (26th June 2015) - Grodecki, Joseph; Short, Aaron R.; Winter, Jessica O.; Rao, Shreyas S.; Winter, Jessica O.; Otero, José Javier; Lannutti, John J.; Sarkar, Atom
<x xml:space="preserve">Abstract</x> Gliomas are highly invasive forms of brain cancer comprising more than 50% of brain tumor cases in adults, and astrocytomas account for ∼60‐70% of all gliomas. As a result of multiple factors, including enhanced migratory properties and extracellular matrix remodeling, even with current standards of care, mean survival time for patients is only ∼12 months. Because glioblastoma multiforme (GBM) cells arise from astrocytes, there is great interest in elucidating the interactions of these two cell types in vivo. Previous work performed on two‐dimensional assays (i.e., tissue culture plastic and Boyden chamber assays) utilizes substrates that lack the complexities of the natural microenvironment. Here, we employed a three‐dimensional, electrospun poly‐(caprolactone) (PCL) nanofiber system (NFS) to mimic some features of topographical properties evidenced in vivo. Co‐cultures of human GBM cells and rat astrocytes, as performed on the NFS, showed a significant increase in astrocyte GFAP expression, particularly in the presence of extracellular matrix (ECM) deposited by GBM cells. In addition, GBM migration increased in the presence of astrocytes or soluble factors (i.e., conditioned media). However, the presence of fixed astrocytes acted as an antagonist, lowering GBM migration rates. This data suggests that astrocytes and GBM cells interact through a multitude of pathways, including soluble factors and direct contact. This work demonstrates the potential of the NFS to duplicate some topographical features of the GBM tumor microenvironment, permitting analysis of topographical effects in GBM migration. © 2015 American Institute of Chemical Engineers Biotechnol. Prog., 31:1406–1415, 2015